Estudo comparativo da influência do ângulo de ataque na resposta dinâmica de um veículo baja - Melo, Maize Cibele de Lima (Universidade Federal Rural do Semi-Árido, 2019)
The Baja is a type of vehicle off-road, that due to its dynamics, gathers various characteristics capable of transpose various types of lands. The SAE BRAZIL proposes engineering students to design and to build these types of vehicle, with intent of promoting competitions of regional, national, and worldwide levels, instigating the involved to search shapes and opportunities of improvements of the projects year after year. The study presents the thematic about the achievement of the study of the influence of the angle of attack in the dynamic answer in the baja vehicle, it were made analysis between two vehicle, in the which have angles of distinct attacks. It was perfomed a analyse about the angle camber, caster, roll center and longitudinal displacement of the front wheels about of the vehicles CT17/18 and SEVERO18/19, produced by team Caraubaja. It put up data leading in consideration the results obtained in the simulations perfomed in softwares and in national and regional competitions, in the which were perfomed static and dynamic comparatives. With help off the softwares Inventor and ADAMS car, it were patterned in 3D, both vehicles. The studies revealed significant diferences in each one of the vehicles, the vehicle CT17/18 which one has minor angle of attack, presented better variation of the roll center, while the vehicle SEVERO18/19 which one has greater angle of attack, presented better varation of the other parameters analyzed, which influenced of positive form the overcoming of obstacles when compared to CT17/18, beyond of reducing the absorption of lateral forces and increase of resistance to efforts. Lastly, it was possible to analyze improvements of project from of the increase of the angle of attack.
Monografia
Keywords: Baja; Análise dinâmica; Ângulo de ataque; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA